2020
DOI: 10.3390/polym12091987
|View full text |Cite
|
Sign up to set email alerts
|

Development of Environmentally Friendly Atom Transfer Radical Polymerization

Abstract: Atom transfer radical polymerization (ATRP) is one of the most successful techniques for the preparation of well-defined polymers with controllable molecular weights, narrow molecular weight distributions, specific macromolecular architectures, and precisely designed functionalities. ATRP usually involves transition-metal complex as catalyst. As the most commonly used copper complex catalyst is usually biologically toxic and environmentally unsafe, considerable interest has been focused on iron complex, enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 189 publications
(224 reference statements)
0
8
0
Order By: Relevance
“…Kwon and Sun studied the reaction mechanism of ethylene polymerization by 1 H/ 13 C Nuclear Magnetic Resonance (NMR) and Density Functional Theory (DFT). [62][63][64] It was found that β-H transfer to aluminum and β-H elimination was the main chain termination pathway, while there also occurred β-H transfer to metal/monomer.…”
Section: Effect Of Ligand Structure On Chain Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Kwon and Sun studied the reaction mechanism of ethylene polymerization by 1 H/ 13 C Nuclear Magnetic Resonance (NMR) and Density Functional Theory (DFT). [62][63][64] It was found that β-H transfer to aluminum and β-H elimination was the main chain termination pathway, while there also occurred β-H transfer to metal/monomer.…”
Section: Effect Of Ligand Structure On Chain Transfermentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Among the numerous catalysts, iron catalysts are becoming attractive owing to their environmental friendliness, low price, and abundant reserves. [10][11][12][13] Nonetheless, the development of these catalysts is hurdled by their wide distribution of polymerization products and poor thermal stability when catalyzing ethylene polymerization. Therefore, developing high-performance ethylene catalysts, reducing the dispersion index (PDI) of polymerization products, and improving the thermal stability of catalysts are the major assignments for their promising industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…Iron is the most abundant transition metal in our planet, and its importance has been well-known, especially with respect to inorganic materials in the steel industry. Iron applications in catalysis have been extended to commercial ethylene oligomerization , and polymerization , as well as living radical polymerization and recently to ring-opening polymerization of various cyclic esters for the synthesis of biodegradable polyesters. In the development of environmentally benign and sustainable materials, polyesters such as polylactide (PLA) and polycaprolactone (PCL) have attracted great attention of researchers because of their biocompatible, biodegradable, and permeable properties; , more importantly the monomers such as lactide (LA) and ε-caprolactone (ε-CL) are completely biosourced, which additionally reduce the threats of fossil resource depletion.…”
Section: Introductionmentioning
confidence: 99%
“…The polymerization of pNIPAm with SP-based monomer can be facilitated by surface-initiated atom transfer radical polymerization (SI-ATRP). In contrast to other polymerization methods, SI-ATRP offers hybrid systems and polymeric materials with tailored micro/nanostructures, tunable sequences, which are important features for various biological and biomedical applications. , Schiphorst et al synthesized NIPAm-SP-functionalized cotton fabrics with light- and temperature-responsive properties for the adsorption and release of moisture from air via ATRP. Ahmadi et al .…”
Section: Introductionmentioning
confidence: 99%